The effect of break-even point analysis in evaluating performance efficiency - an applied study in the General Company for Textile Industries - Hussein Dekan Darwish, (Iraqi Journal for Administrative Sciences, 2024)
The research aims to study the impact of analyzing indicators (the breakeven point) in the process of evaluating performance efficiency at the General Company for Textile Industries as an applied case during the period of economic blockade. The research includes three chapters and concludes that the process of evaluating performance efficiency indicators in the company is generally moral.